Fungsi Pelayanan Terhadap Kepuasan Pelanggan Di Optik Tanjung Padang - Ermi Yusfita (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Customer satisfaction is a crucial factor for the competitiveness of optical clinics in meeting consumer needs. This study aims to analyze the level of customer satisfaction regarding service quality, products, prices, and promotions at Optik Tanjung Padang. The research method employed a quantitative approach through the distribution of questionnaires to 30 respondents (patients). The results indicate that 67% of respondents were satisfied with the services provided, 83% felt comfortable during eye refraction examinations, 70% stated that the service prices were affordable, and 93% considered the product quality to be consistent with the prices offered. Overall, the majority of customers were satisfied with the performance of Optik Tanjung Padang; however, continuous quality improvement remains necessary to maintain customer loyalty amidst business competition.